2023
DOI: 10.3389/fmed.2023.1168977
|View full text |Cite
|
Sign up to set email alerts
|

Missing link between tissue specific expressing pattern of ERβ and the clinical manifestations in LGBLEL

Abstract: PurposeLacrimal gland benign lymphoepithelial lesion (LGBLEL) is an IgG4-related disease of unknown etiology with a risk for malignant transformation. Estrogen is considered to be related to LGBLEL onset.MethodsSeventy-eight LGBLEL and 13 control clinical samples were collected and studied to determine the relationship between estrogen and its receptors and LGBLEL development.ResultsThe serological analysis revealed no significant differences in the levels of three estrogens be-tween the LGBLEL and control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…It has been reported that the NABA MATRISOME ASSOCIATED and NABA SECRETED FACTORS pathways play a key role in breast cancer metastasis through their involvement with extracellular matrix proteins [42,43]. Also, genes linked to the positive regulation of epithelial cell proliferation biological processes are related to the induction of metastasis and inhibition of breast cancer cell apoptosis through the promotion of epithelial cell proliferation via estrogen [44,45]. These results demonstrate the effectiveness of our computational method in unveiling important molecular mechanisms pertaining to breast cancer therapy) that have been approved for breast cancer treatment (see Figure 3) [61][62][63].…”
Section: Dataset1mentioning
confidence: 99%
“…It has been reported that the NABA MATRISOME ASSOCIATED and NABA SECRETED FACTORS pathways play a key role in breast cancer metastasis through their involvement with extracellular matrix proteins [42,43]. Also, genes linked to the positive regulation of epithelial cell proliferation biological processes are related to the induction of metastasis and inhibition of breast cancer cell apoptosis through the promotion of epithelial cell proliferation via estrogen [44,45]. These results demonstrate the effectiveness of our computational method in unveiling important molecular mechanisms pertaining to breast cancer therapy) that have been approved for breast cancer treatment (see Figure 3) [61][62][63].…”
Section: Dataset1mentioning
confidence: 99%